English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-09-15 06:13:31 · 9 answers · asked by Baka_Mochi 2 in Science & Mathematics Mathematics

9 answers

x-6=-5x-2...... Start with the given equation



x=-5x-2+6......Add 6 to both sides



x+5x=-2+6...... Add 5x to both sides



6x=-2+6...... Combine like terms on the left side



6x=4...... Combine like terms on the right side



x=(4)/(6)...... Divide both sides by 6 to isolate x




x=2 / 3...... Reduce


--------------------------------------------------------------

Answer:

So our answer is x=2 / 3 (which is x=0.666666666666667...... in decimal form)

2007-09-15 06:23:41 · answer #1 · answered by Jim 5 · 0 0

Solving for x:
x - 6 = - 5x - 2
6x = 4
x = 2/3

Proof (plug 2/3 for x):
2/3 - 6 = - 5(2/3) - 2
- 5 1/3 = - 10/3 - 6/3
- 5 1/3 = - 16/3
- 5 1/3 = - 5 1/3

2007-09-18 21:41:50 · answer #2 · answered by Jun Agruda 7 · 3 1

First: combine "like" terms - add 5x to both sides (when you move a term to the opposite side, always use the opposite sign).

x - 6+5x = -5x+5x - 2
x - 6+5x = - 2
6x - 6 = - 2

Sec: add 6 to both sides.

6x - 6+6 = - 2+6
6x = 4

Third: solve for "x" by isolating it - divide both sides by 6.

6x/6 = 4/6
x = 4/6 (simplify into lowest terms).
x = 2/3

2007-09-15 06:49:58 · answer #3 · answered by ♪♥Annie♥♪ 6 · 1 0

x - 6 + 6 + 5x = -5x + 5x -2 +6

6x = 4

6x/6 = 4/6

x = 4/6 = 2/3

2007-09-15 06:27:03 · answer #4 · answered by mechnginear 5 · 0 0

Hi, x² + 5x + 6 > 0 (x + 3)(x + 2) > 0 x + 3 = 0 x = -3 <=x intercept x + 2 = 0 x = -2 <=x intercept Since this parabola opens up, it is below the x axis between x = -3 and x = -2. So x² + 5x + 6 > 0 when x < -3 and when x > -2. <==ANSWER I hope that helps!! :-)

2016-05-20 02:56:14 · answer #5 · answered by ? 3 · 0 0

x + 5x = 6 - 2
6x = 4
x = 4 / 6
x = 2 / 3

2007-09-18 23:56:28 · answer #6 · answered by Como 7 · 1 1

x - 6 = -5x -2
x + 5x - 6 = -5x + 5x - 2
6x - 6 = -2
6x - 6 + 6 = -2 + 6
6x = 4
6x/6 = 4/6
x = 2/3

2007-09-15 06:20:52 · answer #7 · answered by Firefly 5 · 0 0

x-6=-5x-2
6x=4
x=2/3 ANS.

2007-09-15 06:35:19 · answer #8 · answered by Anonymous · 0 0

move the x to the otherside and the -2 to the other
you end up with
-4=-6x
divide -4/-6 which equals 2/3
x=2/3

2007-09-15 06:22:26 · answer #9 · answered by msijap 2 · 0 0

fedest.com, questions and answers